THE IMPLICATIONS OF THE APPLICATION OF DIFFERENTIATION FOCUS STRATEGIES TO COMPETITIVE ADVANTAGE AT PRIVATE ISLAMIC EDUCATION INSTITUTIONS - Hifza; Widiyanti, Marlina; Rustam, Andi; Fathani, Abdul Halim; Wahyuni, Purbudi (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study was to analyze the implications of the application of a differentiation focus strategy to the institution’s competitive advantage to private Islamic education, especially to SDIT Ar-Raihan Bantul and SDIT Luqman Al-Hakim Yogyakarta. To understand the implication, this research used a qualitative approach, with phenomenological types of study and multi-site designs. The findings showed that the implications of applying the strategy to institutional competitive excellence to Private Islamic education were as follows: 1) effective leadership in organization of educational institutions; 2) education system that is unique and conducive to the development of the basic potential of students; 3) more images on good school, thereby increasing public trust; and 4) work culture positive in supporting school excellence in a sustainable way.